Gum acacia-based silver nanoparticles as a highly selective and sensitive dual nanosensor for Hg(ii) and fluorescence turn-off sensor for S2− and malachite green detection. Issue 6 (17th January 2020) - Abbasi, Ambreen; Hanif, Summaiya; Shakir, Mohammad
Abstract : Gum acacia-stabilized silver nanoparticles for the detection of Hg(ii ), S 2− and malachite green. Abstract : A facile and green method was adopted to synthesize highly selective gum acacia-mediated silver nanoparticles as dual sensor (fluorescence turn-on and colorimetric) for Hg(ii ) and fluorescence turn-off sensor for S 2− and malachite green. The mechanism proposed for a dual response towards Hg(ii ) is the redox reaction between Ag(0) and Hg(ii ), resulting in the formation of Ag(i ) and Hg(0) and electron transfer from gum acacia to Ag(i ), which further leads to the formation of an Ag@Hg nanoalloy. The enhanced fluorescence signal was quenched selectively by S 2− owing to the formation of Ag2 S and HgS. The reported nanosensor was found to be useful for sensing malachite green via the inner filter effect. The linear ranges were 3 nmol L −1 to 13 μmol L −1 for Hg(ii ), 3–170 μmol L −1 for S 2− and 7–80 μmol L −1 for malachite green, and the corresponding detection limits were 2.1 nmol L −1 for Hg(ii ), 1.3 μmol L −1 for S 2− and 1.6 μmol L −1 for malachite green.